PEMAKAIAN KATA DI MANA DALAM TULISAN MAHASISWA - I Dewa Putu Wijana (Humaniora, 2006)
Generally speakers of bahasa Indonesia use di mana as a question word for asking location of the state or action expressed in information interogative sentences. However, the impact of English usage nowadays made the use of di mana is strongly influenced by English word where to which this Indonesian question word is equivalent. Therefore the use of di mana in students essays writings shows that di mana is not merely functioned as question word, but also as copula, relative clause marker, interclausal and intersentencial conjunctions, and other markers which are difficult to identify because they do not have any equivalent in English.